2019
DOI: 10.1002/cam4.2042
|View full text |Cite
|
Sign up to set email alerts
|

Persistent janus kinase‐signaling in chronic lymphocytic leukemia patients on ibrutinib: Results of a phase I trial

Abstract: Methods to deepen clinical responses to ibrutinib are needed to improve outcomes for patients with chronic lymphocytic leukemia (CLL). This study aimed to determine the safety and efficacy of combining a janus kinase (JAK)‐inhibitor with ibrutinib because JAK‐mediated cytokine‐signals support CLL cells and may not be inhibited by ibrutinib. The JAK1/2 inhibitor ruxolitinib was prescribed to 12 CLL patients with abnormal serum beta‐2 microglobulin levels after 6 months or persistent lymphadenopathy or splenomeg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(42 citation statements)
references
References 36 publications
1
41
0
Order By: Relevance
“…IFN-a2, IFN-g, IL-18, CXCL10, CCL3, and TNF-a were measured as before by Eve Technologies (Calgary, AB, Canada) using Multiplexing LASER Bead Technology (3,22). Concentrations were determined from standard curves.…”
Section: Cytokine Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…IFN-a2, IFN-g, IL-18, CXCL10, CCL3, and TNF-a were measured as before by Eve Technologies (Calgary, AB, Canada) using Multiplexing LASER Bead Technology (3,22). Concentrations were determined from standard curves.…”
Section: Cytokine Measurementsmentioning
confidence: 99%
“…In a prior phase 1 trial, the JAK inhibitor ruxolitinib was added to 12 patients on ibrutinib for 3 out of 5 wk and repeated seven times in an attempt to deepen clinical responses (3). Ruxolitinib blocks signaling through IFNAR and IFNGR along with many other cytokine receptors (3,7,26).…”
Section: Persistent Ifn Signaling In Cll Patients On Ibrutinibmentioning
confidence: 99%
See 1 more Smart Citation
“…87 Therefore, the combination of a JAK inhibitor and ibrutinib can restore the sensitivity of CLL cells to apoptosis, thus rendering a promising alternative treatment for patients with IR. 97 Spaner et al explored the efficacy of the JAK1/2 inhibitor ruxolitinib plus ibrutinib in 12 patients with CLL who did not achieve remission after treatment with ibrutinib, including splenomegaly or persistent lymphadenopathy after 12 months or abnormally elevated serum β-2 microglobulin (β2-MG) levels following 6 months of ibrutinib therapy. 75 Two of the patients achieved PR, and six had diminution of splenomegaly and residual lymphadenopathy; the level of β2-MG decreased during each treatment cycle but was recovered after 2 weeks of interruption of ruxolitinib therapy.…”
Section: Jak1/2 Inhibitorsmentioning
confidence: 99%
“…A pilot study in 2019 suggested the possible role of ruxolitinib in the treatment of Hodgkin’s disease (HD) [ 26 , 27 ]. The effects of ruxolitinib in association with ibrutinib (an FDA approved Bruton’s tyrosine kinase (BTK) inhibitor) against chronic lymphocytic leukemia (CLL) were investigated in a phase 1 study and encouraging results were obtained [ 28 ]. In 2014, ruxolitinib was further approved for the treatment of polycythemia vera (PV) [ 29 ].…”
Section: The Rise Of Jak Inhibitorsmentioning
confidence: 99%